INOVASI PENDIDIKAN DAN PELATIHAN SUMBER DAYA DI DAERAH PESISIR - Junita Kaida'; Eternal Tangke Toban (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Education and training play a very important role in developing the potential of Human Resources (HR) in coastal areas. Amid the complexity of social and economic challenges faced by coastal communities, education and training have a key role in opening up opportunities and overcoming obstacles. This article examines this issue in depth and explores in-depth and comprehensive innovative strategies to improve the quality of education and training in coastal areas. Coastal areas, with their abundant natural wealth, are often considered as potential economic resources. However, behind the natural beauty and abundance of resources, there are complex economic and social challenges. Coastal areas often face pressure from various directions, from climate change to economic instability. Keywords: Economy, innovation, education, coastal, resources